2014
DOI: 10.5614/j.eng.technol.sci.2014.46.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi Method for Development of Mass Flow Rate Correlation using Hydrocarbon Refrigerant Mixture in Capillary Tube

Abstract: The capillary tube is an important control device used in small vapor compression refrigeration systems such as window air-conditioners, household refrigerators and freezers. This paper develops a non-dimensional correlation based on the test results of the adiabatic capillary tube for the mass flow rate through the tube using a hydrocarbon refrigerant mixture of 89.3% propane and 10.7% butane (HCM). The Taguchi method, a statistical experimental design approach, was employed. This approach explores the econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Gawali et al [11], Joshi et al [12] and Dhumal and Dange [13] reported an experimental investigation of the use various expansion valves on the performance of refrigeration system, where TEV provide better performance than other expansion devices. Sulaimon et al [14] investigated the correlation using a mixture of hydrocarbon refrigerant in CT using Taguchi method. Jia and Lee [15] performed experimental study the use of CT and TEV in heat recovery room air-conditioner, the result shows that TEV system gives better performance.…”
Section: Introductionmentioning
confidence: 99%
“…Gawali et al [11], Joshi et al [12] and Dhumal and Dange [13] reported an experimental investigation of the use various expansion valves on the performance of refrigeration system, where TEV provide better performance than other expansion devices. Sulaimon et al [14] investigated the correlation using a mixture of hydrocarbon refrigerant in CT using Taguchi method. Jia and Lee [15] performed experimental study the use of CT and TEV in heat recovery room air-conditioner, the result shows that TEV system gives better performance.…”
Section: Introductionmentioning
confidence: 99%